Pengetahuan Ibu Hamil tentang Kebutuhan Nutrisi Selama Kehamilan - Risa Mundari (Jurnal Ilmu Gizi Indonesia (JIGZI), 2022)
During pregnancy there will be many changes that will be experienced by the mother starting from the cardiovascular system, hormonal, urogenital to the body's metabolism. Along with changes in the mother's body metabolism, the need for nutrients will increase. This increase is needed for the development and growth of the fetus during pregnancy. The nutritional elements needed by pregnant women are carbohydrates, proteins, fats, vitamins and minerals. Of course the need will be more than when not pregnant. The research design used in this research is descriptive, namely the research design that aims to find a description of the phenomena (including health) that occur in a certain population with the aim of knowing a description of the knowledge of pregnant women about nutritional needs during pregnancy at BPM Nurhasanah Gudang Lelang Teluk Betung Bandar Lampung for the January 2021 period as many as 30 pregnant women. Data collection tools and data collection methods in this study were to provide questionnaires to pregnant women who came to visit the period 1 January to 31 January 2021 to BPM. The content of the Questionnaire consists of questions about the benefits of nutrition in pregnancy, nutritional fulfillment during pregnancy, and about the danger signs of malnutrition in pregnancy.  Based on the results of the study, it can be concluded that the knowledge of pregnant women related to the nutritional needs needed during pregnancy is in the poor category. The assessment was carried out by distributing questionnaires with question components which included: the benefits of nutrition during pregnancy, nutritional fulfillment during pregnancy, the respondent's knowledge of the danger signs of nutritional deficiency and nutritional needs during pregnancy. Characteristics of respondents seen from the level of education, employment status and age of pregnant women. Suggestions in this study are the participation of health workers to assist in nutritional needs during pregnancy and the need for improvement of the support system available at BPM such as leaflets to increase knowledge of pregnant women. Keywords: Knowledge, Pregnant Women, Nutrition